The Perception of Early Childhood Education Pre-service Teachers on the Concept of Early Intervention - Berrin Akman; İpek Karlıdağ; Zübeyde Zeynep Özen (Elementary Education Online, 2023)
The purpose of this study is to determine the perception of early childhood education pre-service teachers’ reğardinğ the concept of early intervention throuğh the use of metaphors. For this purpose, metaphors which were developed by early childhood education pre-service teachers were categorized under conceptual themes. Also this study was examined whether developed conceptual themes differ according to variables such as grade level, gender, graduates of high school types, taking education, course or seminar about early intervention. Qualitative method used for data collection. Participants of the study were consisting of 159 pre-service teachers. According to the results of the study, early intervention metaphors developed by early childhood education pre-service teachers were classified under four cateğories: “saver”, “preventer”, “medical intervention” and “benefit”. Considerinğ all of metaphors; first aid, medicine, life-saver, rescue, water, lifeguard and life buoy were the most develop metaphors.